Indicadores bibliométricos em sistemas de informação: uma análise a partir de artigos publicados no Encontro Nacional de Engenharia de Produção - Marques, Márcia Maria (2005)
This research aims at to contribute to show the consolidation of the area of Information Systems (IS) as area of knowledge in Production Engineering. For this, it according to presents a scenery of the publication in IS in the field of the Production Engineering in Brazil amount of articles, the authorship profile, the methodologies, the citations, the research thematic and the continuity of the research thematic. The base for this study was the works published in the National Meeting of Production Engineering - ENEGEP of years 2000, 2001, 2002, 2003 and 2004, inside of the area of Information Systems. Classified as bibliographical research, of applied nature, quantitative boarding, of the point of view of the objectives description-exploration was called and for the collection of data its comment was systematic with bibliographical survey. As field research, the method of collection of data if constituted of the elaboration of an analysis protocol and, to arrive itself at the final diagnosis, it operation the data through the statistical method, with the accomplishment of descriptive analyses. It approached concepts of IS and the seek areas and, it studied research correlate in Production Engineering, in Information Systems, in Information Science and other areas of the knowledge. How much to the results one concluded that the national and international contents are compatible and that the area of IS is in constant evolution. For the continuity of research lines it was observed that the majority of the authors was faithful to the area of Systems of Information. Amongst other found results, some institutions must try to increase its volume of publications and research, while others must look for to keep its reached mark already in the last years